2021
DOI: 10.3390/cancers13092044
|View full text |Cite
|
Sign up to set email alerts
|

Multiregional Sequencing of IDH-WT Glioblastoma Reveals High Genetic Heterogeneity and a Dynamic Evolutionary History

Abstract: Glioblastoma is one of the most common and lethal primary neoplasms of the brain. Patient survival has not improved significantly over the past three decades and the patient median survival is just over one year. Tumor heterogeneity is thought to be a major determinant of therapeutic failure and a major reason for poor overall survival. This work aims to comprehensively define intra- and inter-tumor heterogeneity by mapping the genomic and mutational landscape of multiple areas of three primary IDH wild-type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Firstly, regarding the intertumoral heterogeneity, intrinsic diversities between cancer patients within the same organ are well known and thought to be a major reason for poor overall survival. In this line, many studies reported distinct variations of similar tumor types of different patients [ 35 , 36 , 37 ]. While histopathological and oncological classification showed equal tumor grading, genetic characterization revealed a strong molecular heterogeneity with variances in the mutational analysis as well as in copy number alterations of different genes [ 35 ].…”
Section: Cancer and Cancer Stem Cellsmentioning
confidence: 99%
“…Firstly, regarding the intertumoral heterogeneity, intrinsic diversities between cancer patients within the same organ are well known and thought to be a major reason for poor overall survival. In this line, many studies reported distinct variations of similar tumor types of different patients [ 35 , 36 , 37 ]. While histopathological and oncological classification showed equal tumor grading, genetic characterization revealed a strong molecular heterogeneity with variances in the mutational analysis as well as in copy number alterations of different genes [ 35 ].…”
Section: Cancer and Cancer Stem Cellsmentioning
confidence: 99%
“…It has been found that [ 21 ], ITGB8 (β8 integrin) expression was elevated in GBM stem cells and positively associated with stem cell markers in glioma tissues, and could be induced by hypoxia and p38 activation. DCHS1 (dachsous cadherin-related 1) may belong to some canonical cancer molecular pathways in gliomas [ 22 ] and has been selected as a marker gene in glioma prognostic signature [ 23 ]. Additionally, TGFB2 (Transforming Growth Factor Beta 2) has been identified as a predictor of poor treatment outcomes in pediatric diffuse intrinsic pontine glioma [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In GB, one of the most aggressive brain tumor, there is an urgent demand for novel therapeutic approaches [12]. Unfortunately, recent clinical trials in this field have yielded disappointing results.…”
Section: Introductionmentioning
confidence: 99%